Phytotherapies : efficacy, safety and regulation - Ramzan, Iqbal, 1951- (John Wiley & Sons Inc., 2015)
Variously defined by its practitioners, phytotherapies include herbal therapies, treatments used by indigenous peoples around the world, and alternative medicines to classical western drugs. Despite an increasing trend toward the use of phytotherapies for chemoprevention and management of disease in healthcare, the published work about their efficacy and safety is scattered - and scientists need to understand these key issues along with regulatory aspects of phytotherpeutic agents. A number of herbs are likely to cause adverse effects if not properly standardized in clinical trials. Covering.- Resumé vydavatel
Keywords: fytoterapie -- metody; léčivé rostliny; phytotherapy -- methods; medicinal plants; elektronické knihy; sborníky; electronic books; papers of several authors